Robotic system for magnetic resonance guided focused ultrasound ablation of abdominal cancer - Antoniou, Anastasia; Giannakou, Marinos; Evripidou, Nikolas; Evripidou, Georgios; Spanoudes, Kyriakos; Menikou, Georgios; Damianou, Christakis A. (My University, 2021)
Background A prototype robotic system that uses magnetic resonance guided focused ultrasound (MRgFUS) technology is presented. It features three degrees of freedom (DOF) and is intended for thermal ablation of abdominal cancer. Methods The device is equipped with three identical transducers being offset between them, thus focussing at different depths in tissue. The efficacy and safety of the system in ablating rabbit liver and kidney was assessed, both in laboratory and magnetic resonance imaging (MRI) conditions. Results Despite these organs' challenging location, in situ coagulative necrosis of a tissue area was achieved. Heating of abdominal organs in rabbit was successfully monitored with MR thermometry. Conclusions The MRgFUS system was proven successful in creating lesions in the abdominal area of rabbits. The outcomes of the study are promising for future translation of the technology to the clinic.
Keywords: MRgFUS; Abdominal cancer; Kidney; Liver; Rabbit ablation; Robotic device